Adoption and Impact of Improved Lentil Varieties in Bangladesh 1996-2015 - CGIAR Independent Science and Partnership Council (CGIAR Independent Science and Partnership Council, 2018)
In response to a mid-1980s crisis in lentil production, a joint lentil-breeding program between the International Center for Agricultural Research in the Dry Areas (ICARDA) (http://www.icarda.org/) and Bangladesh Agricultural Research Institute (BARI) (http://www.bari.gov.bd/) led to the release, in 1996, of high-yielding and disease-resistant varieties that mature in less than 115 days. A recent study, funded through the Strengthening Impact Assessment in the CGIAR (SIAC) program 2013-2017 (https://cas.cgiar.org/spia/news/strengthening-impact-assessment-cgiar-siac-2013-2016), documents diffusion of improved lentil varieties in Western Bangladesh. It also attempts to measure the impacts of such diffusion.